2018
DOI: 10.1002/mabi.201800351
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Attachment of Fibronectin onto Emulsion‐Templated Porous Polymer Scaffolds Enhances Human Endometrial Stromal Cell Adhesion, Infiltration, and Function

Abstract: A novel strategy for the surface functionalization of emulsion‐templated highly porous (polyHIPE) materials as well as its application to in vitro 3D cell culture is presented. A heterobifunctional linker that consists of an amine‐reactive N‐hydroxysuccinimide ester and a photoactivatable nitrophenyl azide, N‐sulfosuccinimidyl‐6‐(4′‐azido‐2′‐nitrophenylamino)hexanoate (sulfo‐SANPAH), is utilized to functionalize polyHIPE surfaces. The ability to conjugate a range of compounds (6‐aminofluorescein, heptafluorobu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 44 publications
(63 reference statements)
0
24
0
Order By: Relevance
“…First, they functionalised PolyHIPEs with N-sulfosuccinimidyl-6-(4 -azido-2 -nitrophenylamino hexanoate (sulfo-SANPAH)), which is a photo-linker compound that enables conjugation of biomolecules to the surfaces, and then they further functionalised the surface by covalent attachment of fibronectin to sulfo-SANPAH molecule. An improved cell attachment and infiltration of human endometrial stromal cells have been found when compared to unmodified, just sulfo-SANPAH functionalised, and fibronectin-absorbed (physically) PolyHIPEs (Richardson et al, 2019).…”
Section: Incorporation Of Biomoleculesmentioning
confidence: 96%
See 2 more Smart Citations
“…First, they functionalised PolyHIPEs with N-sulfosuccinimidyl-6-(4 -azido-2 -nitrophenylamino hexanoate (sulfo-SANPAH)), which is a photo-linker compound that enables conjugation of biomolecules to the surfaces, and then they further functionalised the surface by covalent attachment of fibronectin to sulfo-SANPAH molecule. An improved cell attachment and infiltration of human endometrial stromal cells have been found when compared to unmodified, just sulfo-SANPAH functionalised, and fibronectin-absorbed (physically) PolyHIPEs (Richardson et al, 2019).…”
Section: Incorporation Of Biomoleculesmentioning
confidence: 96%
“…The suitability of the morphology of PolyHIPE matrices to be used as TE scaffolds has been well-accepted. However, as PolyHIPEs are most commonly created using w/o emulsions, they are highly hydrophobic, and lack of functionality which limits their interaction with biological tissues ( Richardson et al, 2019 ). Thus, starting from the early 2000s, researchers started to explore the ways of enhancing the biological activities of the PolyHIPE scaffolds using various methods such as chemical functionalisation ( Aldemir Dikici et al, 2019a ), incorporation of the hydrophilic particles such as HA ( Akay et al, 2004 ; Wang et al, 2016 ), incorporation of a single biologically active agent ( Ratcliffe et al, 2019 ; Richardson et al, 2019 ), or decoration PolyHIPEs with cell-derived in vitro generated ECM ( Aldemir Dikici et al, 2020 ; Table 2 ).…”
Section: Development Of the Emulsion Templated Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that certain proteins present in the serum promote cell adhesion (e.g. fi bronectin [12]). Another possibility to enable cell adhesion is coating the cell culture fl asks with collagen, which is an established method to enable cell adhesion [13].…”
Section: Introductionmentioning
confidence: 99%
“…Hematoxylin is alkaline, which makes the chromatin in the nucleus and the nucleic acid in the cytoplasm purple and blue. Eosin is an acid dye that makes the components of the cytoplasm and extracellular matrix reddish . The tails of normal mice show uniform purple and blue structure (Figure a).…”
Section: Resultsmentioning
confidence: 99%